2020
DOI: 10.1186/s12884-020-2787-4
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnostic test for acute fatty liver of pregnancy: a retrospective case control study

Abstract: Background: Early diagnosis is important to lower the mortality rate of acute fatty liver of pregnancy (AFLP). The Swansea criteria is commonly used to diagnose AFLP, but some terms could only be reached when symptoms and signs have progressed, or are not efficient in clinical practice. Therefore, it is necessary to select cost effective tests to simplify and facilitate early suspicion of acute fatty liver of pregnancy. Methods: This is a retrospective study of 28,800 medical records at the Second Xiangya Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
0
9
0
8
Order By: Relevance
“…[ 7 ] Multivariate screening methods based on ultrasound examination and the quantification of diverse maternal urine and serum biomarkers have recently been proposed. [ 8–11 ] Some researchers have developed metabolomic biomarkers for the early pregnancy prediction of preeclampsia. [ 12,13 ] More reliable biomarkers for pregnancy complications are therefore needed to predict potential complications at early gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Multivariate screening methods based on ultrasound examination and the quantification of diverse maternal urine and serum biomarkers have recently been proposed. [ 8–11 ] Some researchers have developed metabolomic biomarkers for the early pregnancy prediction of preeclampsia. [ 12,13 ] More reliable biomarkers for pregnancy complications are therefore needed to predict potential complications at early gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yan et al showed that the sensitivity and specificity of gastrointestinal symptoms +aminotransferase +bilirubin +bile acid +APTT/PT in the diagnosis of AFLP were 97.6% and 97.1% respectively, while more markers may be not conducive to the differential diagnosis. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Liver biopsy is seldom performed and sonographic appearance of a shiny liver is seen only in 25% 3 . Moreover, many components are seen only late in the course of the disease, which renders this score inadequate for early identification 44 . Furthermore, it had poor prediction of the severity of the disease where some but not all parameters were found to predict selected outcome parameters 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Different combinations of individual components of both scoring systems were used to predict the course and outcome of AFLP but failed to produce a clinically useful guide 43,45 . Nevertheless, recently Zhong et al were successful in reaching early diagnosis retrospectively in a statistical model, yet, this has to be confirmed by others in a prospective way 44 . In AFLP, the need for early diagnosis is of utmost importance for two reasons.…”
Section: Discussionmentioning
confidence: 99%